1989
DOI: 10.1104/pp.90.3.1175
|View full text |Cite
|
Sign up to set email alerts
|

Protoporphyrin IX Content Correlates with Activity of Photobleaching Herbicides

Abstract: Several laboratories have demonstrated recently that photobleaching herbicides such as acifluorfen and oxadiazon cause accumulation of protoporphyrin IX (PPIX), a photodynamic pigment capable of herbicidal activity. We investigated, in acifluorfen-treated tissues, the in vivo stability of PPIX, the kinefics of accumulation, and the correlation between concentration of PPIX and herbicidal damage. During a 20 hour dark period, PPIX levels rose from barely detectable concentrations to 1 to 2 nanomoles per 50 cucu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
77
2
4

Year Published

1990
1990
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 128 publications
(87 citation statements)
references
References 34 publications
(42 reference statements)
4
77
2
4
Order By: Relevance
“…'The study was Several laboratories have found the photobleaching DPE2 herbicides to increase greatly the intracellular levels of the photodynamic tetrapyrrole, protoporphyrin, causing light dependent phytotoxic effects (2-4, 6, 14-16, 18, 22-24, 26, 29). DPE herbicides also inhibit Protox, which is the last enzyme of the common branch of the heme and Chl biosynthetic pathways in plants and oxidizes protoporphyrinogen to protoporphyrin (1,5,12,20,21,27,30 (2,19). In addition, these findings are compatible with previous in vivo localization studies in intact plant cells showing that DPE treated plant cells exhibit a rapid accumulation of porphyrins at nonplastidic sites, such as the plasma membrane or in the cytoplasm (16).…”
supporting
confidence: 81%
“…'The study was Several laboratories have found the photobleaching DPE2 herbicides to increase greatly the intracellular levels of the photodynamic tetrapyrrole, protoporphyrin, causing light dependent phytotoxic effects (2-4, 6, 14-16, 18, 22-24, 26, 29). DPE herbicides also inhibit Protox, which is the last enzyme of the common branch of the heme and Chl biosynthetic pathways in plants and oxidizes protoporphyrinogen to protoporphyrin (1,5,12,20,21,27,30 (2,19). In addition, these findings are compatible with previous in vivo localization studies in intact plant cells showing that DPE treated plant cells exhibit a rapid accumulation of porphyrins at nonplastidic sites, such as the plasma membrane or in the cytoplasm (16).…”
supporting
confidence: 81%
“…The lactofen acts in the formation of free radicals in the cytoplasm that are highly reactive in the presence of light and oxygen . the first moments after the application of the herbicide, these radicals cause lipid peroxidation of membranes (Becerril and Duke, 1989), compromising the structure of chlorophyll and optimizing the process of the appearance of chlorotic symptoms. For crops such as soybeans which has selectivity to this herbicide, chlorosis symptoms are common but have a recovery being that the new leaves do not exhibit these symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been reported that the treatment of plants with diphenyl ether and oxadiazon herbicides causes accumulation of excess protoporphyrin IX that acts as a sensitizer for the production of singlet oxygen in the plants. This leads to photodynamic damage and consequent death (3,4,7,27). ALA-induced photodynamic death of the plant could be due to the impairment of various vital functions.…”
mentioning
confidence: 99%